2016
DOI: 10.17795/bhs-40191
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, Thermodynamic and Structural Studies of Native and N-Bromosuccinimide-Modified Mushroom Tyrosinase

Abstract: Background: Mushroom tyrosinase (MT) as a metalloenzyme is a good model for mechanistic studies of melanogenesis. To recognize the mechanism of MT action, it is important to investigate its inhibition, activation, mutation, and modification properties. Objectives: In this study, the chemical modification of MT tryptophan residues was carried out by using N-bromosuccinimide (NBS) and then, the activity, stability, and structure of the native and modified enzymes were compared. Methods: Chemical modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Milla et al [ 40 ] reported pegylation of proteins and liposomes as a strategy for improving the drug delivery. Decrease in activity of mushroom tyrosinase upon modification with N-bromosuccinimide has also been reported by Emami and Gheibi [ 41 ].…”
Section: Discussionsupporting
confidence: 65%
“…Milla et al [ 40 ] reported pegylation of proteins and liposomes as a strategy for improving the drug delivery. Decrease in activity of mushroom tyrosinase upon modification with N-bromosuccinimide has also been reported by Emami and Gheibi [ 41 ].…”
Section: Discussionsupporting
confidence: 65%